Pengaruh Pelatihan dan Pengalaman Kerja terhadap Kompetensi yang Berdampak pada Kinerja Penyuluh Kehutanan Lapangan di Kabupaten Sampang - Kusmaningtyas, Amiartuti (Kajian Manajemen dan Bisnis, 2011)
The government's success in managing land and forest resources can contribute significantly to economic growth and social welfare. These efforts cannot be separated from the performance of Forestry Extension Field in educating the public about the importance of preserving the environment through forest and land rehabilitation. The fact is that in Sampang District, vast wasteland increase year-over-year This indicates that what has been done by a qualified instructor in the Forestry Extension Field in Sampang District in terms of performance is not optimal. Observations and interviews were conducted which imply that the performance is not optimal due to the fact that the Forestry Extension Field has field personnel who are not competent, lacks training and work experience in performing tasks related to the management of the forestry sector Therefore, this research was conducted to analyze the effect of training and work experience to the competencies of field personnel that impact on the performance of Forestry Extension Field. Analysis of the data in that study used descriptive analysis, path analysis model (Path Analysis) and testing hypotheses by using the Statistical Product and Service Solutions (SPSS). The research concludes that there is a significant influence of work experience to competence and competence to performance of Forestry Extension Field and non-significant influence of training to competence, and training and work experience to the performance of Forestry Extension Field.